2001
DOI: 10.1097/00005537-200109000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Mobilization Following Fixation of Mandible Fractures: A Prospective, Randomized Study

Abstract: In this prospective and randomized study, no significant differences were noted between the groups receiving either immediate release or 2 weeks of mandibular-maxillary fixation. The findings support the treatment of selective mandible fractures with 2.0-mm miniplates and immediate mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
(22 reference statements)
1
14
0
2
Order By: Relevance
“…The findings support the treatment of selective mandible fractures with 2.0 mm miniplates and immediate mobilization [25]. The findings support the treatment of selective mandible fractures with 2.0 mm miniplates and immediate mobilization [25].…”
Section: Review Of Literaturesupporting
confidence: 63%
“…The findings support the treatment of selective mandible fractures with 2.0 mm miniplates and immediate mobilization [25]. The findings support the treatment of selective mandible fractures with 2.0 mm miniplates and immediate mobilization [25].…”
Section: Review Of Literaturesupporting
confidence: 63%
“…ORIF of fracture provides stable reconstruction, promotes bone healing, and shortens treatment time [12], allowing immediate jaw mobilization [10].…”
Section: Discussionmentioning
confidence: 99%
“…EMG has been widely used in the evaluation of patients with temporomandibular joint disorders [9,10]. After surgical procedures, EMG is able to monitor the time when the activity of the muscles of mastication is recovered, thus the professional can guide the patient regarding daily activities, type of food, and mastication [8].…”
Section: Introductionmentioning
confidence: 99%
“…The investigators found that both groups healed their fractures but recovery of full mouth opening was more rapid with a shorter period of MMF. In another study addressing the duration of MMF, Kaplan and colleagues 22 Evidence-Based Facial Fracture Management fractures repaired with miniplates plus 2 weeks of postoperative MMF with fractures repaired with no postoperative MMF. They found no differences between the groups in terms of weight loss, trismus, dental hygiene, or wound complications.…”
Section: Angle Fracturesmentioning
confidence: 99%